1993
DOI: 10.1530/jrf.0.0980179
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the duration of exposure to hormone supplements on cytoplasmic maturation of pig oocytes in vitro

Abstract: The effect of hormone supplements on cytoplasmic maturation in vitro was examined by incubating oocyte-cumulus complexes, in a medium with PMSG (10 iu ml-1), hCG (10 iu ml-1) and oestradiol (1 microgram ml-1) for various periods and then transferring them to medium without added hormones for the remainder of the maturation period. Exposure of oocyte-cumulus complexes to hormone supplements for 2 h improved only germinal vesicle breakdown and maturation rates compared with complexes not exposed to added hormone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
101
0
3

Year Published

1996
1996
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(109 citation statements)
references
References 2 publications
5
101
0
3
Order By: Relevance
“…In cattle and mice nearly all oocytes will resume meiosis and the majority (60 to 80%) of those oocytes will progress to MII whether gonadotrophins are present in the medium or not (Sirard and First 1988;Downs et al 2002;Thomas et al 2002;Ali and Sirard 2002). In contrast, reports for porcine oocytes suggest that ,75% of oocytes will undergo GVBD (Laforest et al 2005) but only about half (54%) will achieve metaphase II (Funahashi and Day 1993) in the absence of exogenous gonadotrophins. In our study, only 42% of oocytes cultured in the absence of eCGþEGF reached MII within 24 h of culture, which is similar to the results of Wood et al (1995).…”
Section: Discussionmentioning
confidence: 99%
“…In cattle and mice nearly all oocytes will resume meiosis and the majority (60 to 80%) of those oocytes will progress to MII whether gonadotrophins are present in the medium or not (Sirard and First 1988;Downs et al 2002;Thomas et al 2002;Ali and Sirard 2002). In contrast, reports for porcine oocytes suggest that ,75% of oocytes will undergo GVBD (Laforest et al 2005) but only about half (54%) will achieve metaphase II (Funahashi and Day 1993) in the absence of exogenous gonadotrophins. In our study, only 42% of oocytes cultured in the absence of eCGþEGF reached MII within 24 h of culture, which is similar to the results of Wood et al (1995).…”
Section: Discussionmentioning
confidence: 99%
“…The addition of a suitable hormone supplement to maturation media enhances nuclear maturation and cumulus expansion (Minato and Toyoda, 1982). However, subsequent studies demonstrated that the removal of hormones improved cytoplasm maturation (Funahashi and Day, 1993). Dode and Graves (2002) have indicated that no sexual steroids need to be added to the maturation medium of pig oocytes because COCs secrete steroids during maturation.…”
Section: Discussionmentioning
confidence: 99%
“…However, Kim et al (2011) observed a positive effect of oestrogens on oocyte maturation and early embryo culture during the first half of the IVM period. Funahashi and Day (1993) demonstrated that 20 h of maturation with no hormone supplementation would be necessary to improve cytoplasmic maturation. Based on the regulated sequence of hormonal changes during in vivo maturation, some reports established a two-step IVM system consisting of 22-h incubation with hCG and eCG followed by 22-h incubation with hormone-free media (Marques et al, 2007;Gil et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…COCs containing at least three layers of compacted cumulus cells were selected and cultured in NCSU23 medium [13] supplemented with 0.6 mM cysteine, 10 ng/ml epidermal growth factor (EGF), 10% (v/v) porcine follicular fluid, 75 µg/ml potassium penicillin G, 50 µg/ml streptomycin sulfate, 10 IU/ml eCG (ASKA Pharmaceutical, Tokyo, Japan) and 10 IU/ml hCG (ASKA Pharmaceutical) [14,15]. The COCs were cultured for 22 h with eCG and hCG in a humidified atmosphere of 5% CO2 and 95% air at 38.5 C; This was followed by culture for 22 h without eCG and hCG in an atmosphere of 5% CO 2 , 5% O 2 and 90% N 2 [16].…”
Section: In Vitro Maturation Of Oocytesmentioning
confidence: 99%